Answer:
B=n2 + 6n + 1
Step-by-step explanation:
A = n
B = 2n + 6
C = n^2 - 1
AB - C = n * (2n + 6) - (n^2 - 1) = 2n^2 + 6n - n^2 + 1 = n^2 + 6n + 1
Answer:
The simplest form of the expression AB-C is [tex]n^2+6n+1[/tex].
Step-by-step explanation:
In this exercise we only need to use the properties of arithmetic operations and a minimal knowledge of algebraic notation. We have the expressions
[tex]A = n[/tex],[tex]B=2n+6[/tex],[tex]C=n^2-1[/tex].Now we make the indicated operations, beginning by AB:
[tex]AB=n\cdot(2n+6) = 2n^2+6n[/tex] using the distributive property of multiplication.
Then, we make AB-C:
[tex]AB-C = 2n^2+6n - (n^2-1) = 2n^2+6n-n^2+1 = n^2+6n+1[/tex].
In the last step we must be vary careful with the change of signs in the expression inside parenthesis.
What is the radius and diameter of the following circle?
Answer:
r = 4.2 cm; d = 8.4 cm
Step-by-step explanation:
The radius is the distance from the centre of the circle to the circumference.
r = 4.2 cm
The diameter is the length of a straight line that passes through the centre with each end at the circumference.
d = 2r = 2 × 4.2 cm = 8.4 cm
Answer:
radius=4.2
diameter=8.4
Step-by-step explanation:
(5 x 2)(10^20)^5
what is the answer
Answer:
5 x 2 = 10
(10^20)^5 = 10^100
(10) x (10^100) = 10^101 which is 1 followed by 101 zeroes.
Answer:
10 ^101
Step-by-step explanation:
(5 x 2)(10^20)^5
5*2 = 10
We know a^b^c = a^(b*c)
(10^20)^5 = 10 ^ (20*5) = 10 ^ 100
10 * 10^100
Replacing 10 with 10^1
10^1 * 10^100
We know that a^b * a^c = a^ (b+c)
10^1 * 10^100 = 10 ^(100+1) = 10 ^101
Rewrite the following linear equation in slope-intercept form.write your answer with no spaces. Y-5=3(x+1)
Answer:
[tex]y=3x+8[/tex]
Step-by-step explanation:
Slope-intercept form is as follows:
[tex]y=mx+b[/tex]
In this equation, "m" represents your slope and "b" represents your y-intercept.
To convert your equation into slope-intercept form, distribute your 3 across your parentheses and then add 5 to both sides to isolate for y.
[tex]y-5=3(x+1)\\y-5=3x+3\\y=3x+8[/tex]
The cosine ratio is the ___ side over the hypotenuse
[tex]( - x + 3) - (4x - 10)[/tex]
Answer:
-5x+13 given (-x+3)-(4x-10)
Answer:-5x+13
Step-by-step explanation:
We are going to distribute to get rid of the ( ):
-x+3-4x+10
Pair up like terms:
-x-4x+3+10
Combine the like terms:
-5x+13
Answer:
-5x+13
Step-by-step explanation:
( - x + 3) - (4x - 10)
Distribute the minus sign
( - x + 3) - 4x + 10
Combine like terms
-5x +13
Last week Rachel power walked 2 miles per day on each of the 7 days. During the
same week, she also jogged 5
miles per day on 4 days. What was the total number of
miles Rachel power walked and jogged last week?
Answer: 34 miles
Step-by-step explanation:
First multiply the 2 miles she power walked by the 7 days. (14 miles)
Next, multiply the 5 miles by the 4 days. (20)
Add both numbers, 20+14=34 miles
Which expression is equivalent to 3 square root x^5y
The correct equivalent expression for 3√x⁵y=3 is option c. x⁵/³y
Therefore, after simplification, the equivalent expression to 3√x⁵y is x⁵/³y.
The expression 3√x⁵y represents the cube root of x⁵y. To simplify this expression, let's break it down step by step.
First, we can express 3√x⁵y in exponential form:
3√x⁵y =(3x⁵y)¹/³
Using the property (ab)ⁿ=aⁿ⋅bⁿ, we can separate the terms inside the cube root:
(3x⁵y)¹/³ =3(x⁵/³, y¹/³)
Now, let's look at the options provided:
a. x⁵/³y
b. x⁵/³y¹/³
c. x⁵/³y
d.x⁵/³y³
Comparing the simplified expression 3√x⁵y=3(x⁵/³, y¹/³) to the given options: correct equivalent expression for 3√x⁵y=3 is option c. x⁵/³y.
Which graph shows the piecewise function given below?
The graph that represents the given piecewise function is the one on the right. Therefore the correct answer is option b.
The piecewise function f(x) is defined as follows:
f(x) = -x if x ≤ 3
f(x) = 2 if x > 3
To graph this piecewise function, you would draw two separate segments:
For x values less than or equal to 3, you would graph the line y = -x, which has a negative slope and goes through the point (3, -3). This line represents the function f(x) = -x for x ≤ 3.
For x values greater than 3, you would graph the horizontal line y = 2. This line represents the function f(x) = 2 for x > 3.
The transition from the first segment to the second occurs at x = 3. At this point, you would typically draw an open circle to indicate that the function is defined separately for x ≤ 3 and x > 3.
The graph will consist of a line sloping downward to the left (y = -x) for x ≤ 3 and a horizontal line at y = 2 for x > 3.
Therefore, the correct answer is option b.
Learn more about Analyzing Graphs here:
https://brainly.com/question/12911139
#SPJ3
tate the order and type of each transformation of the graph of the function
ƒ(x) = –(x + 1)3 + 1 as compared to the graph of the base function.
right 1 unit, reflection about the x-axis, up 1 unit
left 1 unit, reflection about the y-axis, up 1 unit
left 1 unit, reflection about the x-axis, up 1 unit
left 1 unit, up 1 unit, reflection about the x-axis
Answer:
left 1 unit, reflection about the x-axis, up 1 unit
Step-by-step explanation:
This is a cubic that has been moved left 1 unit because of the (x+1)^3 part.
It also has been moved up one unit because of the plus 1 on the outside of the cube.
There has also been a reflection across the x-axis because of the -1 in front of the -(x+1)^3 part.
In general, g(x-h)+k means:
1) the function g has been moved right (if h is positive) or moved left (if h is negative).
2) the function g has been moved up (if k is positive) or down (if k is negative)
FGH is a right triangle. True or False?
Your mouse pointer is covering the number at the hypotenuse, but I assume that it is 10.
We can test to see if the triangle is a right angled triangle by using Pythagoras' Theorem. This is because the Pythagorean Theorem only works with right angled triangles.
The theorem is:
[tex]a^{2} + b^{2} = c^{2}[/tex]
where:
a = length of one leg of the triangle
b = length of the other leg of the triangle
c = the length of the hypotenuse.
If triangle FGH is a right triangle then:
[tex]\sqrt{51}^ {2} + 7 ^{2} = 10^{2}[/tex]
[tex]\sqrt{51} ^{2}[/tex] is just 51
[tex]7^{2}[/tex] is 49
and [tex]10^{2}[/tex] is 100
if we add up 51 and 49 we get 100. And of course, 100 = 100,
Since the theorem works, then the FGH is a right triangle
______________________________________
Answer:
True: FGH is a right angled triangle
A bag contains the red marbles, we orange marbles, one yellow marble, and two green marbles. Two marbles are drawn
from the bag
What is the approximate probability of choosing an orange marble and a green marble?
Save and Exit
Submit
Answer:
the answer of this question is 3/5
Answer: the answer is
0.04444
Which of the following statements must be true, given that ABC= XYZ and AB = 10 cm?
Answer:
XY=10 cm
Step-by-step explanation:
Which is a horizontal asymptote of this function?
Answer:
C
Step-by-step explanation:
When both the numerator and denominator of a rational function have the same degree, you divide the highest powered term's coefficients. That is the horizontal asymptote.
Since this function has third degree in both the numerator and denominator, we divide the respective coefficients to find the horizontal asymptote.
So, y = 9/7
Correct answer is C
Note: horizontal asymptote is always in the form y = a (where a is the constant)
4^(4x-1)=32
How do I solve this problem? Do I do 4 to the fourth power first?
Answer:
[tex]\large\boxed{x=\dfrac{7}{8}}[/tex]
Step-by-step explanation:
[tex]4^{(4x-1)}=32\\\\(2^2)^{4x-1}=2^5\qquad\text{use}\ (a^n)^m=a^{nm}\\\\2^{2(4x-1)}=2^5\iff2(4x-1)=5\ \ \text{use the distributive property}\ a(b+c)=ab+ac\\\\(2)(4x)+(2)(-1)=5\\\\8x-2=5\qquad\text{add 2 to both sides}\\\\8x=7\qquad\text{divide both sides by 8}\\\\x=\dfrac{7}{8}[/tex]
What is the volume of the composite figure with the dimensions shown in the 3 views? (Round to the nearest tenth)
Answer:
278.9 units^3 to the nearest tenth.
Step-by-step explanation:
This is a cylinder on the bottom . resting on the cylinder is a prism.
Volume of the cylinder = π r^2 h where r = 1/2 * 7 = 3.5 and h = 6.
V = π * 3.5^2 * 6 = 230.907 units^3.
Volume of the prism = l*w*h
= 4*4*3 = 48 units^3.
Volume of the composite figure = 230.907 + 48
= 278.9.
Six more than the quotient of four and a number xxx.
Answer:
[tex]\large\boxed{\dfrac{4}{x}+6}[/tex]
Step-by-step explanation:
Six more than the quotient of four and a number x:
[tex]\dfrac{4}{x}+6[/tex]
Answer:
[tex]\frac{4}{x}+6[/tex]
Step-by-step explanation:
We have been given a word phrase. We are supposed to represent our given word phrase into an algebraic expression.
The quotient of four and a number x will be 4 divided by x. We can represent this information in an expression as:
[tex]\text{Quotient of four and a number }x=\frac{4}{x}[/tex]
Six more than the quotient of four and a number x would be [tex]\frac{4}{x}+6[/tex]
Therefore, our required expression would be [tex]\frac{4}{x}+6[/tex].
The following list gives the number of siblings for each of 15 students.
2,2,1, 4, 4, 2, 3, 0, 0, 4, 1, 0, 4,0,2
Find the modes of this data set.
Answer:it’s the number that appears most often,so the answer would be 2,4,and 0.
Step-by-step explanation:
The modes of the data set are 0, 2, and 4
Step-by-step explanation:In this question, it is asking you to find the mode of the given data set.
We would be using the data set in the question in order to find out what the mode is.
The mode would be the number that "occurs" the most. In other words, the number(s) that are more "frequent."
Data set:
2, 2, 1, 4, 4, 2, 3, 0, 0, 4, 1, 0, 4, 0, 2
Now, we could count how many of each numbers there are.
0 = 4 (Most)
1 = 2
2 = 4 (Most)
3 = 1
4 = 4 (Most)
When you're done counting the numbers, you would notice that 0, 2, and 4 have the highest number of occurrence in the data set.
This means that the modes of the data set are 0, 2, and 4
I hope this helps you out.Good luck on your academics.Have a fantastic day!Solve for x. Can somebody help me? I don’t understand how to do this.
[tex]-1=\dfrac{5+x}{6}\\\\-6=5+x\\\\x=-11[/tex]
"Solve for x" means get an equation that says " X = something ". It has nothing but X all alone on one side, and the other side tells exactly what X is equal to.
How do you get such an equation ?
-- Take what they gave you in the question.
-- Do anything you want on one side of it, to get X all by itself on that side.
BUT . . .
-- Whatever you do to one side, you must immediately do the same thing on the other side.
Here's how that goes:
Given in the question: -1 = (5 + X) / 6
Multiply each side by 6 : -6 = 5 + X
Subtract 5 from each side: -11 = X
And there you are. It's over almost as soon as it started.
Consider a Poisson distribution with an average of three customers per minute at a local grocery store. IF X = the number of arrivals per minute, find the probability of more than 7 customers arriving within a minute.
Answer:
0.012
Step-by-step explanation:
The probability of more than 7 customers arriving within a minute is obtained by taking the probability at X equal to 0, 1, 2, 3, 4, 5, 6, and 7 then subtracting from the total probability. It can be expected about 1.2% of times that more than 7 customers arriving within a minute.
Answer: 0.0216
Step-by-step explanation:
Given : Average arrivals of customers at a local grocery store = 3 per minute
The Poisson distribution formula :-
[tex]\dfrac{e^{-\lambda}\lambda^x}{x!}[/tex], where [tex]\lambda[/tex] is the mean of the distribution.
If X = the number of arrivals per minute, then the probability of more than 7 customers arriving within a minute will be :-
[tex]\dfrac{e^{-3}(3)^7}{7!}=0.0216040314525\approx0.0216[/tex]
Hence, the probability of more than 7 customers arriving within a minute = 0.0216
Find the product (7v+8)(4v2 - 8v+1)
7v(4v2-8v+1)+8(4v2-8v+1)
28v3-56v2+7v+32v2-64v+8
Answer= 28v3 -24v2 -57v +8
the product of 3 different positive integers is 8 . What is the sum of these integers ?
A : 7
B : 11
C : 13
D : 14
The sum of three positive integers given their product is 7, analyze the factors of the product and sum them up.
The sum of three positive integers whose product is 8 can be found by analyzing the factors of 8.
Given that the product of three different positive integers is 8, the three integers are 1, 2, and 4. Therefore, the sum of these integers is 1 + 2 + 4 = 7.
A circular pie has an area of 706.5 cm2. What is the radius of
the pie?
A)225cm
B)30cm
C)15cm
D)112.5
[tex]\large\boxed{\text{C}).\,15\,\text{cm}}[/tex]
Step-by-step explanation:In this question, we're trying to find what the radius of the circular pie is.
In this question, we know that the area of the pie is 706.5 cm²
We can use the area to find our radius.
We would use the formula [tex]r=\sqrt\frac{A}{\pi}[/tex] to find the radius.
R= radius
A = Area
Your equation should look like this:
[tex]r=\sqrt\frac{706.5}{\pi}[/tex]
Now, you will solve.
[tex]r=\sqrt\frac{706.5}{\pi}\\\\\text{You can make it simpler by turning}\, \pi\,\text{into} 3.14\\\\r=\sqrt\frac{706.5}{3.14}\\\\\text{Divide 706.5 by 3.14}\\\\r=\sqrt225\\\\\text{Now, get the square root of 225}\\\\r=15[/tex]
When you're done solving, you should get 15.
This means that the radius of the pie is 15 cm.
I hope this helped you out.Good luck on your academics.Have a fantastic day!Final answer:
To find the radius of the pie given its area of 706.5 cm², we use the formula A = πr² and solve for r, yielding an approximate radius of 15 cm. This corresponds to option C) on the given list.
Explanation:
To find the radius of the pie given its area, we can use the area formula for a circle: A = πr². Since the area of the pie is given as 706.5 cm², we can rearrange the formula to solve for the radius (r).
The rearranged formula to solve for the radius is: r = √(A/π).
Substituting the given area, we have:
r = √(706.5 cm²/π)
r = √(706.5/3.14159265359)
r ≈ √(225)
r ≈ 15 cm
Therefore, the radius of the pie is approximately 15 cm, making option C) the correct answer.
graph the equations to solve the system
y=-x
y=2x+3
click on the correct answer #1 solutions :all numbers on the line #2 no solutions {} #3 one solution:{-1,1} #4 one solution:{0,3}
Answer:
This system has one solution (-1,1)
Step-by-step explanation:
The attached picture shows the solutions for the system
If we equalize the eq. obtain the following
-x=2x+3
From we obtain that x= -1
Using the first equation y=-x, we obtain that y=1
so (-1,1)
-2y+x=2y-8 what is the y-int and x-int?
Answer:
x-intercept (-8,0)
y-intercept (0,2)
Step-by-step explanation:
To find the x-intercept, you set y equal to 0.
Like this:
-2(0)+x=2(0)-8
0 +x=0 -8
x= -8
So the x-intercept is (-8,0).
To find the y-intercept, you set x equal to 0.
Like this:
-2y+0=2y-8
-2y =2y-8
Subtract 2y on both sides
-4y=-8
Divide both sides by -4
y=2
So the y-intercept is (0,2)
table:
x c(x)
(days) (dollars)
1. 25
2. 45
3. 60
4. 70
Answer:
2) Yes, each x-coordinate is only used once.
3) {1,2,3,4}
4) {25,45,60,70}
5) (3,60)
6) No because (4,7) and (4,25) share the same x-coordinate.
Step-by-step explanation:
A relation is a function if there is no more than one y-value assigned to an x.
Any x used can only be used once in an order pair.
You that here.
(1,25)
(2,45)
(3,60)
(4,70)
So basically because all of the x-coordinates are different, this is a function.
The domain is the x-coordinate of each pair (the first of each pair):
{1,2,3,4}.
The range is the y-coordinate of each pair (the second number of each pair):
{25,45,60,70}.
One ordered pair that I see in the table is (3,60). There are 3 others you can choose and I named them above.
{(4,10),(3,15),(1,5),(2,25),(4,25)} is not a function because there are more than one pairs with the same x-coordinate,4.
Which of the following functions best describes this graph?
A.y=x2+9x+18
B.y=x2-2x+4
C.y=(x-3)(x-6)
The correct equation for the given graph will be option A that is
y=[tex]x^{2} +9x+18[/tex]
What is an equation?
It is a relationship between two variables and having a equal to sign in between.
How to draw a graph?Firstly we need to find the points of the respective equations.
y=[tex]x^{2} +9x+18[/tex]
y=[tex]x^{2}[/tex]+6x+3x+18
y=x(x+6)+3(x+6)
y=(x+3)(x+6)
Put this equal to 0 and we get x=-3 and x=-6
y=[tex]x^{2} -2x+4[/tex]
It is a wrong equation.
y=(x-3)(x-6)
put this equal to 0 we get x=3 and x=6
Now we have to check in the graph whether points (-3,0)(-6,0) satisfies or (3,0)(6,0)
We can easily see that (-3,0)(-6,0) satisfies the graph.
Hence the correct equation is y=x2+9x+18
Learn more about equations at https://brainly.com/question/2972832
#SPJ2
After traveling steadily at 400 meters above a shipwrecked hull, a submerged vessel starts to descend when its ground distance
from the hull is 7 kilometers. What is the angle of depression for this part of the travel?
Select one
O a 1.00
6.327
C 86.73
d. 88.00
Answer:
im trying to find this answer too dont worry :(
Step-by-step explanation:
I dont know
Answer:
Option B, [tex]3.27[/tex]
Step-by-step explanation:
Given -
The submerged vessel travel horizontal distance above the shipwrecked hull
[tex]= 400[/tex]
[tex]= 0.4[/tex] kilometers
The vertical distance from the the shipwrecked hull to the ground is equal to [tex]7[/tex] kilometers
There forms a right angled triangle with
Base [tex]= 7[/tex] kilometer
Perpendicular [tex]=[/tex] 0.4 kilometer
Tan (angle) [tex]= \frac{Perpendicular}{Base}[/tex]
Substituting the given values we get -
Angle of depression
[tex]= tan^{-1}(\frac{0.4}{7})\\= 3.27[/tex]
Hence, option B is correct.
Which lengths would form a right triangle?
O 9, 12, and 14
O 24,7, and 26
o 21, 16, and 12
O 30, 24, and 18
Answer:
O 30, 24, and 18
Step-by-step explanation:
18^2+24^2=30^2
324+576=900
Final answer:
Using the Pythagorean theorem, only the set of lengths 24, 7, and 26 satisfy the condition for a right triangle, as 24² + 7² equals 26².
Explanation:
The question seeks to determine which set of lengths can form a right triangle. When assessing whether a given set of three lengths can form a right triangle, we can use the Pythagorean theorem, which states that in a right triangle, the sum of the squares of the lengths of the two shorter sides (the legs) is equal to the square of the length of the longest side (the hypotenuse). The formula for the Pythagorean theorem is a² + b² = c², where a and b are the lengths of the legs, and c is the length of the hypotenuse.
We will check each set of given lengths:
For lengths 9, 12, and 14: 9² + 12² = 81 + 144 = 225, which is not equal to 14² (196), so this is not a right triangle.For lengths 24, 7, and 26: 24² + 7² = 576 + 49 = 625, which is equal to 26² (625), so this set of lengths can form a right triangle.For lengths 21, 16, and 12: 21² + 16² = 441 + 256 = 697, which is not equal to 12² (144), so this is not a right triangle.For lengths 30, 24, and 18: 30² + 24² = 900 + 576 = 1476, which is not equal to 18² (324), so this is not a right triangle.Therefore, the lengths that would form a right triangle are 24, 7, and 26.
what’s the measure of the missing angles?
Answer:
Angle 1 equals 90 degrees. Angle 2 equals 38 degrees.
Step-by-step explanation:
Angle 1 is at the cross of two perpendicular lines, making it 90 degrees. Angle 2 can be found by making the two equal side lengths and the middle line into one triangle. This means that two of the angles are 52 degrees. This leaves 76 degrees to be split in the triangle. The middle line cuts the angle in half, making it 38 degrees
multiply 5x^2-6x+2 4x^2-3x
Answer:
[tex]20x^{4}-39x^{3} +26x^{2}-6x\\[/tex]
Step-by-step explanation:
Multiply the two polynomials by multiplying each term
[tex](5x^{2} -6x+2)(4x^{2} -3x)\\5x^2*4x^2+5x^2(-3x)+(-6)*4x^2+(-6x)(-3x)+2*4x^2+2(-3x)\\20x^{4}-39x^{3} +26x^{2} -6x\\[/tex]
To multiply the given expressions, use the distributive property and combine like terms. The final result is 20x⁴ - 39x³ + 26x² - 6x.
Explanation:To multiply the expression (5x²-6x+2) (4x²-3x), we can use the distributive property. Multiply the first term in the first binomial (5x²) by each term in the second binomial (4x², -3x), and then multiply the second term in the first binomial (-6x) by each term in the second binomial. Finally, multiply the third term in the first binomial (2) by each term in the second binomial. Combine like terms and simplify as needed to get the final result.
Applying this process, we get:
5x² × 4x² = 20x⁴
5x² × -3x = -15x³
-6x × 4x² = -24x³
-6x × -3x = 18x²
2 × 4x² = 8x²
2 × -3x = -6x
Combining all the terms, we have:
20x⁴ - 15x³ - 24x³ + 18x² + 8x² - 6x
Simplifying further, we get:
20x⁴ - 39x³ + 26x² - 6x
Learn more about the Multiplication of Polynomials here:https://brainly.com/question/34232638
#SPJ11